A Call to Dissent Defending Democracy Against Extremism and Populism - Sim, Stuart 1943- (Edinburgh Edinburgh University Press, 2022)
A rallying cry to defend democracy from the evils of authoritarianism, prejudice, bigotry and apathyLooks at how dissent can counter the move towards dogmatism and authoritarianism in Western democraciesIdentifies a disturbing upsurge in prejudice and bigotry in contemporary politics and explores methods of resisting thisArgues that we should all take part in dissent in our everyday livesDogmatism, prejudice and bigotry are becoming ever more evident in Western politics. Divisive governments looking to cement their power strive to close down anyone who disagrees with them: political opponents, members of their own parties, the mainstream media, educators, protesters and, ultimately, voters. A Call to Dissent defends dissent as an essential part of democracy. Stuart Sim argues that the political left are falling into despair in the face of growing right-wing populism and extremism, rather than challenging and standing up to it. Taking a wide view, he identifies how dissent works in philosophy, religion, science and the arts as well as in politics. Ultimately, he calls on all of us to become dissenters ourselves in order to challenge authority and counter the growth of prejudice and bigotry in public life
Index
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Dissenters; Opposition (Political science); Populism; Right and left (Political science); PHILOSOPHY / Political